PERAN MOTIVASI INTERNAL ATLET BULUTANGKIS UNTUK BERPRESTASI DI KABUPATEN BUNGO - GHAZALI INDRA PUTRA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2019)
This study aims to discuss the role of athletes' internal motivation needed in achieving achievements in badminton. Achievement is the highest dream of an athlete that can be achieved with high motivation. This motivation can come from the athlete's self or outside encouragement. This research focuses on the invasion of badminton athletes to excel. This research is a qualitative research with descriptive method. Data obtained through observation, interviews and documentation studies. The data source in this study is the badminton athletes who are in the club under the guidance of PBSI Bungo district. From the results of data analysis it can be concluded that, athletes who are in PBSI fostered by Bungo district are so motivated to excel in badminton. This motivation arises from the desire to become like a champion, so that life can prosper like an idol athlete and want to enter print or electronic media.